2011
DOI: 10.1038/jcbfm.2011.117
|View full text |Cite
|
Sign up to set email alerts
|

Selective CDK Inhibitor Limits Neuroinflammation and Progressive Neurodegeneration after Brain Trauma

Abstract: Traumatic brain injury (TBI) induces secondary injury mechanisms, including cell-cycle activation (CCA), which lead to neuronal cell death, microglial activation, and neurologic dysfunction. Here, we show progressive neurodegeneration associated with microglial activation after TBI induced by controlled cortical impact (CCI), and also show that delayed treatment with the selective cyclin-dependent kinase inhibitor roscovitine attenuates posttraumatic neurodegeneration and neuroinflammation. CCI resulted in inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 46 publications
6
108
0
1
Order By: Relevance
“…33 Our analysis was focused on the dorsal region of the hippocampus, in the area directly underneath the impact site. The sampled region for each subfield was demarcated in the injured hemisphere and cresyl violet neuronal cell bodies were counted.…”
Section: Assessment Of Neuronal Cell Loss In the Hippocampal Sub-regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Our analysis was focused on the dorsal region of the hippocampus, in the area directly underneath the impact site. The sampled region for each subfield was demarcated in the injured hemisphere and cresyl violet neuronal cell bodies were counted.…”
Section: Assessment Of Neuronal Cell Loss In the Hippocampal Sub-regionsmentioning
confidence: 99%
“…Lesion volume was determined based on the Cavalieri method as previously described. 33 The lesion area, including both the cavity and surrounding damaged tissue, was outlined using the Stereologer 2000 program (Systems Planning and Analysis, Alexandria, VA) to obtain the final volume measurements.…”
Section: Lesion Volume Assessmentmentioning
confidence: 99%
“…In addition, cyclin dependent kinase (CDK) inhibitors can reduce neuronal death, suppress reactive glia, and improve neurological outcomes in a number of acute and chronic neurodegenerative disorders [33,[35][36][37][38][39][40][41][42][43]. Little is known about the role of cell cycle genes in neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Studies have demonstrated that TBI induces cell cycle activation (CCA) that may result in apoptosis of postmitotic cells (mature oligodendroglia and neurons) and activation of mitotic cells (microglia and astrocytes). [4][5][6][7][8][9] Microglial and astrocyte activation is associated with the release of proinflammatory molecules that can cause neurotoxicity. 5 Therefore, TBI-induced CCA may initiate multiple secondary injury mechanisms that directly and indirectly contribute to neuronal apoptosis and delayed neurotoxicity, respectively.…”
Section: Introductionmentioning
confidence: 99%